From nanoscience to nanotechnology: what can and what cannot be manufactured. (21st April 2014) - Kelly, Michael J.
Only a small fraction of contemporary nanoscience will ever emerge as a functioning and commercial nanotechnology. Far too little attention is paid to the hoops and hurdles presented by the transition from science to technology by those who assert that their work will find applications. A systematic protocol is developed for appropriate investigations.